Densification of the Ground-Based GNSS Observation Network in the Southwest Indian Ocean: Current Status, Perspectives, and Examples of Applications in Meteorology and Geodesy - Bousquet, Olivier; Lees, Edouard; Durand, Jonathan; Peltier, Aline; Duret, Anne; Mekies, Dominique; Boissier, Patrice; Donal, Thomas; Fleischer-Dogley, Frauke; Zakariasy, Lova (Frontiers in Earth Science, 2020)
In the frame of the research project IOGA4MET, a new ground-based GNSS network is being deployed in the Southwest Indian Ocean (SWIO) since November 2017. This new network opens up for new research opportunities in geodesics and atmospheric sciences in this area regularly exposed to natural hazards, and significantly expands the International GNSS System (IGS) network, which only includes eight stations so far in the SWIO. After a description of the current status of IOGA4MET, examples of regional applications in meteorology (climatology and numerical modelling) and geodesy (monitoring of ground deformations) are presented using data collected in northern Madagascar and small neighboring islands in 2018-2020. The observed water vapor cycle is shown to exhibit different characteristics and important variability at all locations. At the seasonal scale, maximum IWV values are similar everywhere, minimum values decrease away from the equator and a sharp IWV gradient can be noticed during the wet-dry transition period. At this time scale, the seasonal IWV cycle analyzed with the high-resolution NWP system AROME-IO matches observations with little discrepancies . At the diurnal scale, IWV characteristics show different behavior on each side of Madagascar, which emphasizes the important role of this island in driving the regional circulation. Finally, examination of ground displacements measured by GNSS stations in relationship with the ongoing Mayotte seismic-volcanic crisis indicates that ground deformation associated with the current off-shore volcanic activity east of Mayotte does not extend up to 250 km, or is currently too low to be detected in very far field.